Mind-Wandering Mediates the Associations Between Neuroticism and Conscientiousness, and Tendencies Towards Smartphone Use Disorder - Müller, Marko; Sindermann, Cornelia; Rozgonjuk, Dmitri; Montag, Christian (Frontiers in Psychology, 2021)
Mounting evidence suggests that smartphone overuse/smartphone use disorder (SmUD) is associated with negative affectivity. Given a large number of smartphone users worldwide (currently about 4.7 billion) and the fact that many individuals carry their smartphones around 24/7, it is of high importance to better understand the phenomenon of smartphone overuse. Based on the interaction of person-affect-cognition-execution (I-PACE) model, we investigated the links between SmUD and the personality traits, neuroticism and conscientiousness, which represent two vulnerability factors robustly linked to SmUD according to a recent meta-analysis. Beyond that, we tested the effects of mind-wandering (MW) and fear of missing out (FoMO) in the relation between individual differences in personality and tendencies towards SmUD. The effective sample comprised 414 study participants (151 men and 263 women, age M = 33.6, SD = 13.5). By applying a structural equation modeling (SEM) technique, we observed that the associations of higher neuroticism and lower conscientiousness with higher levels of SmUD were mediated by higher scores in mind-wandering. These novel findings can help to understand the associations between personality and SmUD in more detail.